Церква, політика та ЗМІ: від маніпулятивних технологій до рівноправної комунікації - Козиряцька, Світлана (Видавництво Львівської політехніки, 2018)
Such problem of the religious journalism as depicting of religious events in the context of state political life is defined. The engagement of the confessional media and the lack of the balanced content on religious topics in the secular media are underlined. One of the causes of possible manipulations of the public opinion with the help of the confessional and secular media is established. The necessity of the existing of socially responsible journalism is justified.
Keywords: релігійна журналістика; конфесійні медіа; комунікація; журналістські стандарти; інформаційно-комунікативний простір